The Malkus-robbins dynamo with a Nonlinear Series Motor. - Moroz, I (2004)
In a recent paper Moroz [2003] considered a simplified version of third class self-exciting Faraday-disk dynamo model, introduced by Hide [1997], in the limit in which leads to the Malkus -Robbing dynamo [Malkus, 1972; Robbins, 1977] as a special case. In that study a linear series motor was incorporated which led to an enriching range of possible behavior that the original Malkus-Robbins dynamo could support. In this paper, we replace the linear motor by a nonlinear motor and consider the consequences on the dynamics of the dynamo.